The Effect of Innovation in Business Model, Services and Technology on Firm Sustainability: An Examination using Triple Bottom Line Theory - Faisal, Fatin Faseha; Muhammad, Kamaruzzaman; Ghani, Erlane K (The Economics and Finance Letters, 2022)
Recent studies have suggested one way to strengthen firm sustainability is through innovation. Innovation can be very flexible as it can be applied to many different aspects, such as the innovations in products or services, technology, marketing, or the business model itself. This study examines the effect of innovation on firm sustainability. Specifically, this study examines the effect of innovation in the aspects of business model, services, and technology on the sustainability of a company in the retail and merchandise industry. Using a questionnaire survey distributed to the employees of the company as the research instrument, this study shows that innovations in services and technology do impact firm sustainability. However, the findings also show that innovation in the business model does not impact firm sustainability. The findings of this study contribute to the literature and provide further evidence of the importance of innovation in increasing firm sustainability. In addition, the findings may also provide companies with a broader perspective on how innovation can affect their sustainability.